Graphene-Doped Titanium Niobate for the Hydrogen Production - Samara Letiéle dos Santos; Annelise Kopp Alves (Materials Research)
Great efforts have been made to develop new energy sources that can replace conventional energy sources that rely on fossil resources. The present study aims to develop electrocatalysts of Titanium Niobate doped with Graphene at concentrations of 0.01%, 0.02% and 0.05%, to produce hydrogen through the electrolysis of natural seawater, using the dip-coating technique. The electrocatalysts were characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), diffuse reflectance and linear voltammetry to analyze the thermal properties, morphology, band gap and electrolytic performance, respectively. The films were tested in an electrolytic cell known as Hoffman's voltmeter with natural seawater as the electrolyte, their efficiency in generating hydrogen was evaluated by gas chromatography. Preliminary results have shown that catalysts are effective in the electrolysis of water, producing hydrogen with significant percentages of the element, making it a promising alternative for sustainable fuel generation.